2022
DOI: 10.1038/s43587-022-00276-y
|View full text |Cite
|
Sign up to set email alerts
|

Males induce premature demise of the opposite sex by multifaceted strategies

Abstract: Interactions between the sexes negatively impact health in many species. In Caenorhabditis, males shorten the lifespan of the opposite sex—hermaphrodites or females. Here we use transcriptomic profiling and targeted screens to systematically uncover conserved genes involved in male-induced demise in C. elegans. Some genes (for example, delm-2, acbp-3), when knocked down, are specifically protective against male-induced demise. Others (for example, sri-40), when knocked down, extend lifespan with and without ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…One of the most upregulated genes, sri-40 (Fig. 1h ), was also significantly induced in whole body after mating with males and, when reduced, extends lifespan with and without males, suggesting its involvement in general protection of mating-induced death 34 . Genes downregulated in the mated germline include metabolic processes (rRNA, cellular aromatic compound and heterocycle metabolic process) (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…One of the most upregulated genes, sri-40 (Fig. 1h ), was also significantly induced in whole body after mating with males and, when reduced, extends lifespan with and without males, suggesting its involvement in general protection of mating-induced death 34 . Genes downregulated in the mated germline include metabolic processes (rRNA, cellular aromatic compound and heterocycle metabolic process) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4a ). Since the pro-aging signal originates from the germline, it must be germline-specific; we subtracted those genes that are also upregulated in mated glp-1 germlineless worms 34 from the original list, reducing the number of candidates to 418 ( Source Data , Fig. 4a and Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, interactions with males are detrimental to C. elegans hermaphrodites (Shi and Murphy 2014; Ting, et al 2014; Booth, et al 2022) and some of this effect is due to male-excreted compounds (Maures, et al 2014; Shi, et al 2017). Previously, we showed that ascr#10 shortens the hermaphrodite lifespan (Aprison and Ruvinsky 2016; Ludewig, et al 2019).…”
Section: Resultsmentioning
confidence: 99%